Post-thermal annealed monolayer graphene healing elucidated by Raman spectroscopy - Lee, Mei Bao; Lee, Chiew Tin; William Chong, Woei Fong; Wong, King Jye (Springer Nature, 2023)
The inconsistent conductivity and surface roughness of commercially available chemical vapour deposition (CVD) monolayer graphene films have limited their widespread adoption in optoelectronic devices. This study presents a novel approach to address this issue by investigating the effect of post-thermal annealing on the sheet resistance (Rs) and surface properties of CVD monolayer graphene films on quartz substrates. The films undergo thermal annealing at temperatures ranging from 200 to \(600\,^{\circ }\hbox {C}\) in a nitrogen environment using a one-zone tube furnace. Remarkably, annealing the graphene films at \(400\,^{\circ }\hbox {C}\) leads to a remarkable reduction in Rs by 58.1% and surface roughness (Ra) by 33.3%. In-depth analysis using Raman spectroscopy reveals that the Rs reduction is attributed to increased charge density from doping effects, while the Ra reduction is attributed to thermal-induced mechanical biaxial tensile strain. Moreover, the Raman spectrum exhibits a remarkable 67.3% reduction in the quality–intensity ratio (\({I}_\textrm{D}\)/\({I}_\textrm{G}\)) of the graphene film annealed at \(400\,^{\circ }\hbox {C}\), confirming a defect-free state, and further validating the healing effect on the commercially procured graphene films. These findings offer great potential for enhancing the performance and reliability of commercially available CVD monolayer graphene films in optoelectronic devices. By introducing a practical solution to improve conductivity and surface roughness, post-thermal annealing at an optimal temperature of \(400\,^{\circ }\hbox {C}\) presents a promising and innovative approach to unlock the full potential of CVD monolayer graphene films in various technological applications